The Utilization of Noni leaf Silage (Morinda citrifolia L.) with Marine Yeast Inoculant in Feed to Growth of Kissing Gouramy (Osphronemus gouramy Lac.) - Deana, Anri M Shaleh; Suharman, Indra; ', Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research aims to determine the effect of noni leaf silage on food efficiency and growth of kissing gouramy (Osphronemus gouramy Lac.) using the experimental method, completelly randomized design with one factor, five treatments and three replication which had different level comparison of soy bean meal and noni leaf silaged meal, spesifically P1 (100%TK : 0%TSDM), P2 (90% TK : 10%TSDM), P3 (80% TK : 20%TSDM), P4 (70% TK : 30%TSDM), dan P5 (60% TK : 40%TSDM). The result indicated that feed with addition noni leaf silage meal on 10, 20, 30, and 40% were significant effect (P<0.05) on feed effiency, and very significant effect (P<0,01) on protein retention and average specific growth. The best treatments is obtained on P5 addition noni leaf silage as much as 40% with average feed efficiency of 26.57%, protein retention of 25.27%, spesific growth rate 2.32%/day, feed digestived of 72,83% and survival rate of 97%. Key word : Noni leaf, silage, Kissing Gouramy